The politics of age and disability in contemporary Spanish film : plus ultra pluralism - Marr, Matthew J. (Routledge advances in film studies ;, 2013)
"The Politics of Age and Disability in Contemporary Spanish Film examines the onscreen construction of adolescent, elderly, and disabled subjects in Spanish cinema from 1992 to the present. Applying a dual lens of film analysis and theory drawn from the allied fields of youth, age, and disability studies, this study is set both within and against a conversation on cultural diversity--with respect to gender, sexual, and ethnic identity--which has driven not only much of the past decade's most visible and fruitful scholarship on representation in Spanish film, but also the broader parameters of discourse on post--Transition Spain in the humanities. Presenting an engaging, and heretofore under-explored, interdisciplinary approach to images of multiculturalism in what has emerged as one of recent Spain's most vibrant areas of cultural production, this book brings a fresh, while still complementary, critical sensibility to the field of contemporary Peninsular film studies through its detailed discussion of six contemporary films (by Salvador García Ruiz, Achero Mañas, Santiago Aguilar & Luis Guridi, Marcos Carnevale, Alejandro Amenábar, and Pedro Almodóvar) and supporting reference to the production of other prominent and emerging filmmakers"--